2019
DOI: 10.1186/s12904-019-0441-6
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care for persons with Parkinson’s disease: a qualitative study on the experiences of health care professionals

Abstract: Background Parkinson’s disease (PD) is a chronic and neurodegenerative disease associated with a wide variety of symptoms. The risk of complications increases with progression of the disease. These complications have a tremendous impact on the quality of life of people with PD. The aim of this study was to examine health care professionals’ experiences of potential barriers and facilitators in providing palliative care for people with PD in the Netherlands. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 49 publications
1
47
0
14
Order By: Relevance
“…We further developed elements that could be helpful in implementing ACP in practice. As earlier studies [5,14,15,55] describe difficulties in role and responsibility on this topic in PD, we found consensus on statements that give direction on how, what and by whom ACP could be performed. Our findings suggest that healthcare professionals of all disciplines do have a role or are entitled to introduce ACP.…”
Section: Plos Onementioning
confidence: 55%
See 2 more Smart Citations
“…We further developed elements that could be helpful in implementing ACP in practice. As earlier studies [5,14,15,55] describe difficulties in role and responsibility on this topic in PD, we found consensus on statements that give direction on how, what and by whom ACP could be performed. Our findings suggest that healthcare professionals of all disciplines do have a role or are entitled to introduce ACP.…”
Section: Plos Onementioning
confidence: 55%
“…Although the potential need for palliative care is increasingly acknowledged, still little is known about effective and useful components in PD patients [4,5,14]. There is no clear conceptualization of palliative care in PD and as a result, many healthcare professionals experience difficulties in providing palliative care [15][16][17][18]. A typical general misconception is that palliative care is associated with cancer, terminal phase care or dying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 displays the result of the searches. An additional two publications were identified through forward and backward citation tracking [5,23]. They were published after the date of our electronic search and included after screening for relevance.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…Despite studies exploring ACP in neurodegenerative conditions [5][6][7], international working groups concluded that there is a lack of research in ACP [8,9]. However, ACP should be considered in PD and atypical parkinsonian disorders, as these progressive conditions lead to increasing disability due to physical and neurobehavioural symptoms with advancing disease, although disease progression is variable [9].…”
Section: Introductionmentioning
confidence: 99%